Salicylic acid and soil cover in the cultivation of physalis (Revista de Ciências Agroveterinárias, 2023)
The objective of this work was to verify the influence of the application of different concentrations of salicylic acid and different soil coverings in the cultivation of physalis (Physalis peruviana L). The work was developed in the experimental area of ​​the Federal University of Fronteira Sul, Laranjeiras do Sul-PR. Physalis seedlings produced in a greenhouse were used. The field was subjected to five concentrations of salicylic acid (0, 0,001, 0,002, 0,003, 0,004 Mol L-¹), and three soil coverings (grass straw, eucalyptus and control without straw). In the pre-harvest evaluations, the experimental design was randomized blocks, in a 3x5 factorial scheme. For post-harvest evaluations, the experimental design was 3x5x2, and the month of harvest was also considered. There was no interaction between the factors for the analyzed variables. For height and diameter increase and presence of insects, incidence and severity of leaf diseases, only the factor of salicylic acid influences. In the post-harvest period, only the month of harvest interfered in the factors, with the September harvest having the largest number and mass of fruits, but also the greatest attack by insects and diseases. It was concluded with this work that the application of salicylic acid influenced the development of physalis plants.
Keywords: Physalis Peruviana L; Elicitors; Resistance induction; mulching